Compulsory license to utilize the patent in accordance with UAE law and in light of the TRIPS Agreement - Abdallah Hameed Al Ghuwairi, (Technium Social Sciences Journal, 2020)
The study deals with legal texts dealing with compulsory licensing to exploit an invention, covered by legal protection in accordance with UAE law and TRIPS, the researcher follows the curriculum. Descriptive analysis and comparison of texts dealing with compulsory licensing in UAE Law. In the light of the TRIPS Agreement, the study focused on determining what is meant by compulsory licensing The right to grant a compulsory license in the event that they are available to the judiciary or cases where the UAE law permits the Minister to grant the license Compulsory with the conditions to be granted for the granting of compulsory license in each case of Cases in which UAE law and the TRIPS Agreement permit the compulsory licensing of third parties.The study examines the conditions for granting a license Compulsory and its legal effects, the study was divided into two subjects, and the section of each topic to two requirements, in addition to a conclusion containing the most important findings and recommendations.